Longitudinal Bone Mineralization Assessment in Children Treated With Long‐Term Parenteral Nutrition for Severe Intestinal Failure. Issue 3 (15th December 2017) - Poinsot, Pierre; Geoffroy, Perrine; Braillon, Pierre; Denis, Angelique; Loras‐Duclaux, Irene; Marotte, Stéphanie; Boutroy, Stéphanie; Bacchetta, Justine; Touzet, Sandrine; Lachaux, Alain; Peretti, Noel
Abstract: Background : Metabolic bone disease is common in children receiving home parenteral nutrition (HPN) for intestinal failure (IF). Long‐term evolution of bone mass in pediatric IF is poorly documented. The aims of this study were (1) to determine the prevalence of low bone mass (LBM) in children receiving HPN for IF, (2) to evaluate the evolution of total bone mineral content (TBMC) during HPN with dual‐energy x‐ray absorptiometry (DXA), and (3) to identify related factors. Methods : All children referred in our HPN center from 2004 to 2014 were eligible. Inclusion criteria were HPN dependence due to noninflammatory IF, at least 2 TBMC assessments, and HPN duration of at least 2 years at last DXA. TBMC was expressed in z score for ideal weight for height (WFH). LBM was defined by a TBMC WFH z score ≤–2 standard deviations (SD). Results : A total of 175 DXAs for 31 children were performed, mean of 5.6 ± 2.9 assessments per child. The median time between first and last DXA recorded was 6.2 years (0.7–16.6). At the first DXA, 14 children (45%) had a LBM. TBMC increased by +0.1 ± 0.04 SD per year of HPN ( P = .012). The risk of LBM decreased with an odds ratio of 0.9 per year of HPN (95% confidence interval, 0.92–0.99; P = .018). Lean mass z score and calcium parenteral intakes were related to the TBMC improvement. Conclusion : LBM is common in pediatric IF, but bone status could improve during HPN in these children.